The impact of helmet use on outcomes after a motorcycle crash. Issue 5 (May 2017) - Khor, Desmond; Inaba, Kenji; Aiolfi, Alberto; Delapena, Samantha; Benjamin, Elizabeth; Matsushima, Kazuhide; Strumwasser, Aaron M.; Demetriades, Demetrios
Abstract: Background: Helmet use in a motorcycle collision has been shown to reduce head injury and death. Its protective effect on the cervical spine (C-spine), however, remains unclear. The objective of this study was to explore the relationship between helmet use and C-spine injuries. Method: Retrospective National Trauma Data Bank (NTDB) study. All motorcycle collisions between 2007 and 2014 involving either a driver or passenger were included. Data collected included demographics, vital signs, Abbreviated Injury Scale (AIS), Injury Severity Score (ISS) and specific injuries. The primary outcome was the prevalence of C-spine injuries. Secondary outcomes included were overall mortality, ventilation days, intensive care unit length of stay (LOS), total hospital LOS, and in-hospital complications. Results: A total of 270, 525 patients were included. Helmets were worn by 57.6% of motorcyclists. The non-helmeted group was found to have a higher incidence of head injury with head AIS > 2 (27.6% vs 14.8%, p < 0.001). Univariate analysis showed a higher prevalence of C-spine injuries in the non-helmeted group (10.4% vs 9.4%, p < 0.001), with a higher proportion of severe C-spine injuries with AIS > 2 (3.2% vs 2.6%, p < 0.001). Additionally, traumatic brain injury (TBI) was found to be two times higher in the non-helmeted group (20.7% vs 10.9%, p < 0.001). Multiple logistic regression showed helmet use to be an independent protective factor against mortality (OR = 0.832, 95% CI 0.781–0.887, p < 0.001). Although statistically significant in univariate analysis, helmet use was not associated with C-spine injuries after adjusting for relevant covariates. However, helmet use reduced the risk of severe head injuries by almost 50% (OR = 0.488, 95% CI 0.475–0.500, p < 0.001). Conclusions: Helmet use reduces the risk of head injury and death among motorcyclists; however, no association with C-spine injuries could be detected.